2006
DOI: 10.1111/j.1365-2591.2006.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage along Glassix glass fibre posts cemented with three different materials assessed using a fluid transport system

Abstract: Canals with Glassix posts cemented with Variolink II and Fuji PLUS cement had the least leakage when assessed using a fluid transport system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…Works using dyes, although showing limitations, have still been used to verify the capacity of cementing agents [29,30]. The literature shows that the cementing of pins with zinc phosphate cement has higher apical contamination rates [31,32], which was confirmed in this study during the daily control, since all the specimens were infected within 29 days. The results of this study showed no significant difference in relation to bacterial infiltration, when glass ionomer and resin cements were compared.…”
Section: Discussionsupporting
confidence: 72%
“…Works using dyes, although showing limitations, have still been used to verify the capacity of cementing agents [29,30]. The literature shows that the cementing of pins with zinc phosphate cement has higher apical contamination rates [31,32], which was confirmed in this study during the daily control, since all the specimens were infected within 29 days. The results of this study showed no significant difference in relation to bacterial infiltration, when glass ionomer and resin cements were compared.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, primary stability of inserted root canal posts is of major importance for the postendodontic restoration; consequently, the use of glass ionomer-based cements for clinical application should be questioned. In addition, the coronal sealing quality of adhesively luted posts is superior compared with that of conventionally luted posts (22).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it must be pointed out that the clinical use of zinc phosphate cement, as luting material for fiber posts, needs further investigation. It has already been shown to have a low potential for sealing the root canal wall and a lack of adhesion to the surface of the post (21,22).…”
Section: Discussionmentioning
confidence: 99%